Transient elevation of anti-transglutaminase and anti-endomysium antibodies in Giardia infection. (3rd July 2018) - Hanevik, Kurt; Wik, Elisabeth; Langeland, Nina; Hausken, Trygve
Abstract: Markers of celiac disease (CeD) may be elevated in various conditions of intestinal inflammation or autoimmune disease. Recent reports argue that intestinal infection may induce development of CeD in susceptible individuals. Serum anti-tissue transglutaminase (tTG) and anti-endomysium antibodies (EMA) have been proposed in previous reports to be helpful in differentiating between giardiasis and CeD. In this report, we describe eight cases with elevated CeD serological markers and pathological duodenal histology during, or shortly after, Giardia infection. We present follow-up clinical and serological findings to determine which of these that were diagnosed with CeD. Serum levels of tTGand EMA did not discriminate well between patients where CeD was excluded, and those who were later diagnosed with CeD. The value of these serological CeD markers is discussed in relation to CeD diagnosis in cases with chronic or recent giardiasis.